2019
DOI: 10.1101/782920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of cytokinesis by β-adrenergic receptors indicates an approach for regulating cardiomyocyte endowment

Abstract: ABSTRACT/SUMMARYOne million patients with congenital heart disease (CHD) live in the US. They have a lifelong risk of developing heart failure. Current concepts do not sufficiently address mechanisms of heart failure development specifically for these patients. We show that cardiomyocyte cytokinesis failure is increased in tetralogy of Fallot with pulmonary stenosis (ToF/PS), a common form of CHD. Labeling of a ToF/PS baby with isotope-tagged thymidine showed cytokinesis failure after birth. We used single-cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…In mammals, evidence suggests that the predominantly mononucleated and diploid state of embryonic/fetal cardiomyocytes is essential for the high proliferation rates observed in these hearts [ 13 , 20 , 21 , 22 , 23 ]. During postnatal cardiomyocyte cell cycle arrest, karyokinesis (nuclear division) in the absence of cytokinesis (cell division), also known as endoreplication, results in predominantly binucleated cardiomyocytes in a post-mitotic quiescent state within 10 days after birth in rodents ( Figure 1 A) [ 13 , 21 , 24 , 25 ].…”
Section: Overview Of Postnatal Cardiomyocyte Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, evidence suggests that the predominantly mononucleated and diploid state of embryonic/fetal cardiomyocytes is essential for the high proliferation rates observed in these hearts [ 13 , 20 , 21 , 22 , 23 ]. During postnatal cardiomyocyte cell cycle arrest, karyokinesis (nuclear division) in the absence of cytokinesis (cell division), also known as endoreplication, results in predominantly binucleated cardiomyocytes in a post-mitotic quiescent state within 10 days after birth in rodents ( Figure 1 A) [ 13 , 21 , 24 , 25 ].…”
Section: Overview Of Postnatal Cardiomyocyte Maturationmentioning
confidence: 99%
“…Direct perturbation of cytokinesis in proliferating cardiomyocytes leads to loss of regenerative potential in both zebrafish and neonatal mice, supporting a causative role [ 13 , 26 ]. Cardiomyocyte polyploidization also contributes to the injury response in adult cardiomyocytes, which undergo maladaptive multinucleation or increased nuclear polyploidization in disease/injury conditions [ 22 ]. Thus, cardiomyocyte polyploidization may be both a consequence of, and directly responsible for, the transition from a fetal-like proliferative state to a post-mitotic terminally-mature state.…”
Section: Overview Of Postnatal Cardiomyocyte Maturationmentioning
confidence: 99%
“…Cardiomyocytes can be mono-, bi-, or multi-nucleated, and their nuclei can become polyploid. Current research in cardiomyocyte proliferation focuses on understanding the block at cell-cycle entry and the mechanisms inhibiting the completion of cytokinesis (Soonpaa et al, 1996;Liu et al, 2019). However, the existence of polyploid nuclei in mono-and binucleated cardiomyocytes indicates that, besides the cell-cycle blocks at entry and cytokinesis, additional cell-cycle mechanisms exist that generate polyploid nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of various species offer clues about the relationship between nucleation, ploidy, and capacity for proliferation. It is thought that myocardial regeneration requires proliferation of mononucleated cardiomyocytes with diploid nuclei because both observations and experimental studies in various species have shown that increased polyploidy reduces heart regeneration (Gonzá lez-Rosa et al, 2018;Hirose et al, 2019;Liu et al, 2019;Patterson et al, 2017). In mice, the prevalence of cardiomyocytes with polyploid nuclei increases within 3 weeks after birth (Alkass et al, 2015;Walsh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Signaling through adrenergic receptors reportedly modulates various cellular functions or properties, including (but not limited to) cell cycle and proliferation (91,92), migration (93), and cytokine (94) and antibody (95) production. Although historically, signaling through β-ARs has often been associated with anti-inflammatory outcomes, in more recent years, the ability of β-ARs to mediate context-dependent, pro-and antiinflammatory effects has become more widely appreciated (29,94,96).…”
Section: Catecholamine Signaling Pathwaysmentioning
confidence: 99%